Optimal design of washcoated monolith catalyst for compact, heat -integrated ethanol reformers. (3rd May 2019) - Kaur Sidhu, Tejas Puneet; Roy, Shantanu
Abstract: Monolith reactors are extensively employed for adiabatic gas-solid reactions, primarily in environmental applications. They are emerging as an attractive application in catalytic reformers where hydrogen needs to be produced on-board. These uses of monoliths are based on the optimal configuration and geometry of the washcoat, i.e., the thin catalytic layer impregnated onto the inert backbone of the monolith. In this paper, we present an analysis of the influence of geometric parameters of the washcoated monolithic catalyst towards affecting the reactor performance of non-isothermal reactor operation. The reactor performance is accounted through 'volumetric reactor activity' which comprises of the transport-kinetic interactions under adiabatic reactor condition. The effects of different combinations of the radius of curvature and coating thickness on the reactor activity and effectiveness factor are investigated for different backbone geometries. Through this process, an optimal combination of ( R, d h ) for each backbone configuration is evaluated. The radius of curvature ( R  = 0) always gives highest reactor activity due to low mass transfer resistance obtained in corners. With the increase in washcoat loading, the reactivity increases and after a certain point, it decreases owing to the mass transfer resistance which starts dominating at beyond that point. Finally, a 3D monolith geometry is modeled, and its performance is evaluated through ethanol conversion and temperature variations while the reforming section is coupled with ethanol combustion. Parametric sensitivity analysis is also performed by varying the effective diffusivity, the reaction rate constant, reforming section inlet velocity and feed temperature. Highlights: Washcoated monolith reactor design for heat-integrated steam reforming of ethanol. Optimal design of the heat integrated monolith block presented through CFD modelling. Optimum washcoat layer thickness and corner curvature is elucidated. Method may be extended for optimal design of washcoated monoliths for any gas phase application.